2021
DOI: 10.7759/cureus.13832
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Giant Cell Tumor of the Occipital Skull Base: A Case Report and Literature Review

Abstract: Giant cell tumor of bone is a benign but locally aggressive osteolytic neoplasm that represents 3% to 5% of all primary bone tumors, primarily found at the epiphyses of long bones. Less than 1% are of calvarial origin. Herein, we report a rare case of a nine-year-old girl with a hemorrhagic giant cell tumor of the left occipital skull base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…[12] However, some series have reported slight female or male predominance. [21,24,51] In our review of reported cases in the occipital region, most patients were female adults; interestingly, the youngest patient was a 10-day male newborn [Table 1]. GCTB has also been reported in patients with neurofibromatosis, aneurysmal bone cysts, and Paget's disease; however, there is no clear association, and risk factors remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[12] However, some series have reported slight female or male predominance. [21,24,51] In our review of reported cases in the occipital region, most patients were female adults; interestingly, the youngest patient was a 10-day male newborn [Table 1]. GCTB has also been reported in patients with neurofibromatosis, aneurysmal bone cysts, and Paget's disease; however, there is no clear association, and risk factors remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[2,12] Particularly, few cases have been reported in the occipital bone compared to the temporal, frontal, sphenoid, and ethmoidal bones. [4][5][6][7]13,[15][16][17]19,[21][22][23]26,[28][29][30][31]33,37,43,45,[47][48][49]51,[53][54][55] Weng et al reported that the overall distribution of cases in the occipital bone was 9.8%. [51] is tumor is more common among adults, and gender distribution has been previously reported to be more common in females.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations